ANALYZING THE IMPACT OF COLLEGE OF AMERICAN PATHOLOGISTS LABORATORY (CAP) ACCREDITATION PROGRAM ON POSTANALYTICAL ERROR (The Research of Medical Science Review, 2024)
This study investigates the impact of College of American Pathologists (CAP) accreditation on post-analytical errors in a clinical laboratory, with a focus on errors in data entry, delayed reporting, critical value communication, and report formatting. Post-analytical errors, which occur after the completion of sample analysis, can significantly affect patient outcomes and clinical decision-making. Using a comparative pre- and post-accreditation approach, data were collected and analyzed over two 12-month periods—one year before (June 2021 - May 2022) and one year after (June 2022 - May 2023) CAP accreditation. Results show a substantial reduction in total post-analytical errors following accreditation, with a decrease from 945 to 643 errors, representing a 31.9% improvement. Specifically, errors in delayed reporting decreased by 34.8%, data entry inaccuracies by 27.3%, misfiled reports by 30.4%, and incorrect critical value communication by 30.6%. These findings align with existing literature, confirming that CAP accreditation contributes to enhanced laboratory performance through standardized quality management practices. The study underscores the clinical importance of CAP accreditation, linking it to improved accuracy and timeliness in laboratory reporting, which are essential for optimal patient care. Our findings support CAP accreditation as an effective intervention for reducing post-analytical errors, and further recommend that laboratories consider additional quality improvement initiatives focused on sustaining error reductions over time.